An approach to cultural management in the archaeological site of Cajamarquilla, Lima- Peru - Cáceres Ramos, Benito (2021)
In the present article, the final reports of archaeological interventions are reviewed, and from that review an approach to the archaeological heritage management in the archaeological site of Cajamarquilla was described. The final reports provide information concerning the investigation, conservation, diffusion and protection of the archaeological monument. Also, in relation to the diffusion and protection it describes the function that fulfills the Cajamarquilla’s center of Interpretation implemented in the year 2010; the foregoing indicates that we are dealing with the presence of cultural heritage management. In the final part of the text, some recommendations are made where it is considered important the participation of the different actors to protect and manage the archaeological site.